The VOC lodge of Wingurla (Bulletin KNOB, 1996)
Wingurla - the present Vengurla - was one of the few Indian trading posts that had a political function apart from its commercial one. Notably its situation - approximately 60 kilometres to the north of Goa - explains the significance of this lodge. Wingurla was the VOC (East India Company) settlement closest to the Portuguese centre of power Goa; during the forties and fifties of the seventeenth century this greatest threat to the VOC could be followed closely from here, until Portuguese power was definitely broken in the battle of Cochin around 1663. By means of the architecture of the building the founders of the lodge, in 1637, obviously intended to underline its strategic and commercial significance. Among the very austere VOC architecture this lodge with its vaults and cassette stuccowork is really an exceptionally beautiful building.The main building measures 75 x 44 Rhineland feet and consists of two levels; originally it had a roof construction. In this originally oldest part the rooms are spanned by cross vaults, on the first floor adorned with cassette stuccowork. The remnants of this stuccowork are still visible. Originally the lodge was surrounded by an earth rampart. Shortly after 1643 a start was made with the circumvallation with two bastions. Obviously, the lodge had not been built very solidly, for in 1655 accidents were reported, probably caused by the dilapidated state of the lodge. Subsequently, the gallery and roof construction were renovated.Later, in the eighteenth century, various other renovations and modernizations were carried out, among which the construction of the present four bastions. The gateway building was also enlarged. In the course of the nineteenth century the south-western corner of the main building was restored. This part had apparently been destroyed or become dilapidated, so that this had to be prematurely repaired in a simple manner. The lodge must have started to decay at the end of the sixties of this century.Thanks to a photo documentary by Mr Barendsen from 1971 we still have an impression of the building in a good state. In spite of the fact that the Archaeological Survey of India - the authority charged with the management of the building - appointed a watchman here to keep the premises clean, the building is in a very bad condition now. In 1994 the authors measured and examined the building elaborately.